Study of systematic Literature review in Education: Paul Ricoeur in focus (Research, Society and Development, 2021)
This study is a Systematic Literature Review, at Manancial - Digital Repository of the Federal University of Santa Maria. Its purpose is to identify research at the Master and Doctorate level that focuses on the productions and thinking of the philosopher Paul Ricoeur. The research findings were subjected to treatment of qualitative analysis data, allowing to identify their specificities in the research context. The data points to the plurality of possibilities that the Repository has, as well as a series of publications that are linked to the conceptual and approach emphasis arising from Ricoeur's understanding, mainly in the Postgraduate Program in Philosophy, pointing to its potential for exploration in other areas, such as the education area.